Drama Mun-Tangan Alif: Representasi Kosmologi Sunda-Islam - Dwimarwati, Retno - (PANGGUNG, 2012)
ABSTRACTÃÂ Mun-Tangan Alif is a Sundanese drama which is full of religiosity depicting one who is going through the steps toward the Creator (God). Sunda cosmology in this drama reveals the existing life in dasaring bumi, madyapada, and jabaning langit. The religiosity of Mun-Tangan Alif represents the human beingÃ¢â¬â¢s consciousness as the GodÃ¢â¬â¢s creation with obedience and appropriate efforts to be always in His ways. The awareness of time cycle and struggle for the highest degree gives the under- standing to reach the true life with truth values, either in Sunda or Islam. Analysed by using Pavis method, it can be seen that Mun-Tangan Alif can mediate the peopleÃ¢â¬â¢s consciousness of how to be Sundanese in exploring, understanding, and applying local (Sundanese) wisdom in life.ÃÂ Keywords: Sunda cosmology, local wisdom, drama.ÃÂ ÃÂ